Managerial Competencies and Performance of Small and Medium Enterprises in Yangon, Myanmar - Hlaing, Su Wah; Aung, Myo Myint (International Journal of Financial, Accounting, and Management, 2025)
Purpose: This study explores the effect of managerial competencies on the performance of SMEs in Yangon, Myanmar. Methods: A mixed-method approach was employed, combining qualitative and quantitative data. A structured questionnaire was distributed to 370 SMEs in Yangon, selected through a stratified random sampling technique, and regression analysis was used for quantitative data. In addition, 10 participants were interviewed for the qualitative portion, and thematic analysis was applied to the qualitative data. Results: The quantitative findings indicate that managerial skills positively impact SME performance, although the influence of certain competencies on business outcomes differs depending on the firm's size. Qualitative analysis revealed that while most SMEs acknowledged the significance of conceptual and technological skills, they were less aware of the importance of human competencies. Furthermore, respondents highlighted the necessity of significant investment to promote business growth and innovation, but these requirements were largely neglected by the government. Conclusions: This study found that managerial competencies significantly influence SME performance in Yangon, with technical skills being crucial for small businesses and broader competencies for medium-sized businesses. Many SME owners lack awareness of human competencies and face ongoing challenges, particularly limited government support for investment and innovation. Limitations: This study focuses exclusively on SMEs in Yangon, which may not provide a comprehensive representation of the broader SME sector in Myanmar. Contribution: The findings of this study are anticipated to offer valuable insights to SME operators, owners, and policymakers in Myanmar.